Acute sprint performance responses to velocity-based versus traditional post activation performance enhancement interventions - Murat Tutar; Sümeyye Genç; Atakan Çağlayan; Erkan Günay (PLoS ONE, 2025)
The aim of this study was to compare the acute effects of velocity-based training (VBT), traditional strength training (TSG) and a non- strength control condition (CG) on sprint performance in trained individuals. In Session 1, anthropometric measurements of the participants were taken, and then 1 repetition maximum (1RM) squat values were determined after explanation, visual demonstration and familiarization of the sprint test and VBT method. In the second session, all participants performed a sprint test for the control condition. In the third session, participants completed the post activation performance enhancement (PAPE) protocol specific to their group after a standard warm-up and then performed sprint tests. In the 0–10 m distance, only the group × time interaction was significant (p = .014); a performance decrease (p = .016) was observed in the TSG group. In the 0–20 m sprint, time (p < .001), group (p = .043), and interaction (p = .003) effects were significant, and a significant performance increase was found in the VBT and TSG groups (p < .001). In the 0–30 m sprint, group (p = .015) and interaction (p < .001) effects were significant; an improvement was observed in the VBT group (p < .001) and a decrease in the TSG group (p = .039). In conclusion, this study demonstrated that the VBT protocol produced a more noticeable acute improvement in sprint performance compared to TSG, even when applied with the same load absolute.